Consumer Dirtwork: What Extraordinary Consumption Reveals about the Usefulness of Dirt - Warren, Nathan B; Price, Linda L (Journal of Consumer Research, 2025)
Abstract Societies create material, social, and moral boundaries that define who and what is dirty. “Dirt” encompasses literal and figurative things—objects, beings, ideas—that transgress these boundaries and thus are “out of place.” Previous research describing how consumers avoid and manage dirt assumes that dirt is aversive. The concept of consumer dirtwork emerged from our examination of self-described “dirtbag” wilderness consumers. Dirtwork reveals the potential usefulness of dirt. Instead of cleaning, dirtworkers redraw dirt boundaries, revealing resources they then work to capture. Boundary redrawing describes a continuum of adjustments to dirt boundaries, ranging from small shifts to complete inversions. Resourcing work describes the efforts required to capture the resources that are uncovered by boundary redrawing. Dirtwork results in challenges and rewards, and offers the possibility of continued dirtwork-resourced consumption. Dirtwork contributes by revealing the process wherein consumers make use of dirt, thus demonstrating the usefulness of dirt and fluidity of dirt boundaries. Dirtwork provides a useful lens for understanding consumer behaviors that do not aspire or cannot conform to socially-imposed cleanliness rules, including stigmatized, mundane, and extraordinary consumption. Dirtwork challenges assumptions that clean is good, socially-valuable, safe, and sustainable, and implicit associations of dirt with danger, stigma, and unsustainability.